Onscreen Allusions to Shakespeare
XV, 225 p. 13 illus., 11 illus. in color.
Keywords: Allusions to Shakespeare haunt our contemporary culture in a myriad of ways, whether through brief references or sustained intertextual engagements. Shakespeare’s plays and motifs have been appropriated in fragmentary forms onstage and onscreen since motion pictures were invented in 1893. This collection of essays extends beyond a US-UK axis to bring together an international group of scholars to explore Shakespearean appropriations in unexpected contexts in lesser-known films and television shows in India, Brazil, Russia, France, Australia, South Africa, East-Central Europe and Italy, with reference to some filmed stage works. Alexa Alice Joubin is founding Co-Director of the Digital Humanities Institute and Professor of English, Women’s, Gender and Sexuality Studies, Theatre, East Asian Languages and Literatures, and International Affairs at George Washington University in Washington, D.C., USA. Her latest book is Shakespeare and East Asia (2021). Victoria Bladen teaches literary studies and adaptation at the University of Queensland, Australia. Her latest book is The Tree of Life and Arboreal Aesthetics in Early Modern Literature (2021).